The Effect of the inquiry wheel model on the chemical enlightenment of Second- Year intermediate School female Students (Journal of the College of Basic Education, 2025)
The aim of the research was to know the effect of the inquiry wheel model on chemical enlightenment among second-grade middle school female students in government daytime middle and secondary schools. Umm Al-Qura Middle School was chosen by intentional selection to be its students as the research sample for the academic year (2024-2025). Two groups were chosen, one of which was the experimental group studying using the inquiry wheel model and the other the control group studying in the usual way. The equivalence of the two research groups was verified by a set of variables, which were (chronological age in months, previous information test, Raven's intelligence test, chemical enlightenment scale). As for the research tool, the researchers built a chemical enlightenment scale and applied the scale to the two groups. It was found that there were statistically significant differences at the level (0.05) between the average scores of the students of the two experimental groups who studied according to the inquiry wheel model and the control group who studied according to the usual method in favor of the experimental group. Its validity, stability and psychometric properties were verified, and the results were analyzed using statistical methods. In light of this, recommendations and conclusions were made.